High-precision quality assurance of robotic couches with six degrees of freedom. (May 2018) - Cheon, Wonjoong; Cho, Junsang; Ahn, Sung Hwan; Han, Youngyih; Choi, Doo Ho
Highlights: A high precision automatic QA system is developed for robotic couch QA. Visual tracking system (VTS) using motion capture cameras were used. The new system offered QA of yaw, pitch and roll motion and sagging of the couch. The new system has sub-millimeter/degree accuracy. Abstract: A robotic couch capable of six degrees of freedom (6-DoF) of motion was introduced for state-of-the-art radiation therapy. Patient treatment requires precise quality assurance (QA) of 6-DoF. Unfortunately, conventional methods do not provide the requisite accuracy and precision. Therefore, we developed a high-precision automated QA system using a visual tracking system (VTS). The VTS comprises four motion-sensing cameras, a cube with infrared reflective markers. To acquire data in treatment room coordinates, a transformation matrix from VTS coordinates to treatment room coordinates was determined. The mean error and standard deviation of linear and rotational motions, as well as couch sagging were analyzed from continuously acquired images in the moving couch. The accuracy of VTS was 0.024 mm deviation for the sinusoidal motion, and the accuracy of the transformation matrix was 0.02 mm. In a cross-comparison, the difference between Laser Tracker (FARO) measurements was 0.14 ± 0.12 mm for translation and 0.032 ± 0.026° on average for yaw rotation. The new system provides QA of yaw, pitch and roll motion as well as sagging of the couch and sub-millimeter/degree accuracy together with precision.